High-risk human papillomaviruses L1 gene isolates identified in Western Kazakhstan - Saule K. Balmagambetova; Elena V. Zholdybayeva; Oxana V. Zavalennaya; Ainur Amanzholkyzy; Victoria I. Kononets; Gulmira M. Zharmakhanova; Nadiar M. Mussin; Lazzat M. Zhamaliyeva; Nurgul M. Kereyeva (National Scientific Medical Center, 2024)
Kazakhstani researchers reported a significant prevalence of highly carcinogenic human papillomavirus types in the country. The article aimed to present HPV L1 gene sequencing developments in women affected with cervical cancer throughout the western part of Kazakhstan with provided findings on the geographic pathways of obtained isolates. Methods. The HPV L1 gene was amplified using the consensus primers MY09HPV 5'-CGTCCMARRGGAWACTGATC-3' and MY11HPV 5' - GCMCAGGGWCATAAYAATGG-3'. The purified DNA was used as the target for direct nucleotide sequencing. Phylogenetic analyses were conducted using the MegAlign program from the LASERGENE software package (version 6.0; DNA star, Madison, WI) and with MEGA version 5.0 software. A multiple alignment was created through Clustal W software, and the neighbor-joining method was used to construct the phylogenetic tree. Results. Of 70 HPV samples transported to the Astana shared laboratory for gene L1 sequencing, only ten appeared fit to obtain isolates (14.3%). The viral load of the samples ranged from 3.3 to 8.2, and the range of DNA concentration was from 8.16 to 69.6 ng/uL. HPV16 unique Kazakhstani isolate from Aktobe, having its own branch, and not yet registered in the world genebank, was revealed. An isolate of potentially carcinogenic HPV53 forming a remote cluster with KF436822/1, KU951264.1 - Southwest China, and 97% identity with EU056643.1 - Ireland, and acted as a single agent for invasive cervical cancer was identified. In general, the sequencing findings indicate the variety of ways for HPV pervasion into the western region of Kazakhstan: North and South America, Europe, and Asia. The study was recorded in the ISRCTN registry, No. 7154910, 02/01/2018.